Pengaruh Kegel Exercise terhadap Inkotinensia Urin pada Lansia - Erika Nurwidiyanti (Jurnal Keperawatan Notokusumo, 2014)
Background : Urinary incontinence is one of seriously problems that usually comman in elderly. Many chronically conditions can appear if incontinence urine did not treated early since the symptoms cammon. Kegel exercise is one of early interventions that can be given to the urinary incontinence’s patient in order to decrease that symptom. Good understanding about incotinence urine is needed to treating this problem well. Objective : To know the influence kegel exercise for elderly incontinence urine. Method : The purpose of this study was to know the effect of “kegel exercise” to urinary elimination disorder (incontinence urine) in elderly. This research is pra- experiment research; one graup pretest- posttestdesign where the sample was collected with purposive sampling. There are 15 elderly womens who are more than 45 years old as the subject. They are member of The Centre of Elderly Services of Mangir Tengah Village at 2008. The subject was interviewed directly before and after they did kegel exercise among 6 weeks, with usewd questionnaire of urinay elimination disorder that focused on the symptoms of urinary incontinence chronic persistent. Result : The findings of this study revealed that “kegel exercise” has significant effect to decrease disorder of urinary elimination (incontinence urine) in elderly with p value 0,002, escpecially disorder to stoped the stream of the urine when urinate with p significant 0,005 and difficult to stand the urinewith p significant 0,059. This findings support the hypothesis of the research, so it can be a guide to the elderly nurses, the workers of The Centre of Elderly Services, and medical workers to practice kegel exercise as the early intervention to the symptoms of urinary elimination disorder (incontinence urine) in elderly. Conclusion : There are influence which significan kegel exercise for decrease elderly incontinence urine. Key words: elderly, kegel exercise, urinary incontinence